Integrating Digital Pedagogy and TQM in Islamic Religious Education: A Mixed-Methods Study in Indonesian Madrasahs to Enhance Teacher Competence and Learning Quality - Samsuddin Samsuddin; Abdurrahman Abdurrahman; Abdul Jabar; Nurwahida Nurwahida; Mowafg Masuwd (IJCRE - International Journal of Culture, Religion, and Education, 2026)
This study aims to analyze the integration of Total Quality Management (TQM) and digital pedagogy in Islamic Religious Education (IRE) within Indonesian madrasahs to enhance teacher competence and instructional quality. Using a mixed-methods approach, the research combined quantitative correlation analysis with qualitative interviews, observations, and document analysis. The results revealed a positive and significant relationship between TQM implementation and teachers’ digital pedagogical competence (r = 0.64; p < 0.01). Qualitative findings showed that institutional and technological barriers—such as limited digital infrastructure and internet access—remain major challenges, especially in rural madrasahs. However, strong leadership commitment and a culture of continuous improvement were found to mitigate these constraints and foster innovation. The integration of TQM and digital pedagogy also aligns with moral and spiritual dimensions in Islamic education, indicating that digital media can serve as both pedagogical and ethical tools for character formation. The study concludes that sustainable improvement in Islamic education requires leadership grounded in moral integrity, reflective practice, and a continuous quality culture.